MEKANISASI PERTANIAN MELALUI INOVASI TRAKTOR BAJAK SAWAH RAKITAN DENGAN PENGGERAK MESIN MOTOR BEKAS - diki triyudi refindo (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
The agricultural sector is a source of food supplies. One of the problems that farmers often face in agricultural business is that they still use traditional technology so it is less effective. This research aims to innovate a rice plow tractor using an assembly with a used motor engine. Manufacturing is divided into 3 processes, namely the pre-production process, production process and post-production process. The results of the research produced a rice plowing tractor driven by a used motor engine which has been tested and implemented in several rice fields in Wonogiri Regency. The advantages of the